MICROBIOLOGICAL QUALITY OF CAYENNE PEPPER (Capsicum frutescens L.) IN MALANG TRADITIONAL MARKET - Abdul Fattah Noor; Utami Sri Hastuti; Betty Lukiati (BIOLINK (Jurnal Biologi Lingkungan Industri Kesehatan), 2023)
Cayenne pepper is consumed as a food spice because of its color, spicy taste, aroma and complete nutritional value. Cayenne pepper sold in traditional markets is not separated between whole cayenne pepper and broken cayenne pepper. This study aims to: 1) calculate the ALT of mold colonies on whole and damaged cayenne peppers, 2) identify contaminant mold species found in intact and damaged cayenne peppers. Samples of whole cayenne pepper and damaged cayenne pepper were isolated by grinding 10 grams of cayenne pepper, it was then inoculated on Potato Dextrose Agar (PDA) medium and incubated at 25oC for 7 x 24 hours. Then the ALT of mold colonies was calculated on whole and damaged cayenne pepper. Then, each isolated mold contaminating colony's morphology and microscopic characteristics were described. Finally, each contaminant mold isolate was identified. Furthermore, the study unpacked that: 1) The ALT of contaminant mold colonies on whole cayenne pepper was 1.0x103 colonies/g, while the average ALT of contaminant mold colonies on damaged cayenne pepper was 2.1x105 colonies/g, 2) There were 8 species of mold found in cayenne pepper namely Mucor racemosus Fres, Aspergillus niger van Tieghem, Penicillium griseofulvum Dierckx, Penicillium frequentans Westing, Penicillium citrinum Thom, Penicillium nalgiovense Laxa, Penicillium digitatum Sacc and Penicillium variabile Sopp.